The spiritual writings of Amir ʻAbd al-Kader - ʻAbd al-Qādir ibn Muḥyī al-Dīn, Amir of Mascara, 1807?-1883 (SUNY series in Western esoteric traditions., 1995)
Behind 'Abd al-Kader's role of brilliant warrior lay another, that of spiritual master in the direct lineage of Ibn 'Arabi, the Shaikh al-Akbar (the greatest shaikh). The thirty-nine texts translated here were chosen because they represent the major themes of the teaching of 'Abd al-Kader. Many are commentaries on passages from the writings of Ibn 'Arabi. They offer a rare opportunity to share the illumination of a master writing from his own direct experience. -- Back cover.